Kapitalisme Digital dalam Media Sosial Youtube: Kritik Terhadap Perkembangan Teknologi Digital Berdasarkan Pemikiran Herbert Marcuse - Ishaq, Anton; Saksono, Eko Hari (Jurnal Mahardika Adiwidia, 2023)
The development of digital technology which is so rapid at this time has an impact on changes in various lines of society. One of the changes in behavior and new habits can be seen in how people interact with various digital technology platforms that are used as channels of communication and socialization. Through these various digital platforms, the public can not only easily obtain information, but can also process and produce information. The change in role from consumer to producer is one of the influences of technology that drives society today to be in the information society era. However, user-generated content basically generates huge profits for social media operators through user-produced content and of course, also comes from advertisements. This monetization is perceived by users as an opportunity to earn income through social media. Thus, users are competing in various ways to produce content in order to achieve monetization in accordance with the terms and conditions of social media operators. On the one hand, it seems that these social media users are not aware that their existence in social media is basically an instrument of the system contained in social media itself. The data in this article was carried out by analyzing a number of YouTube application YouTuber accounts and conducting an analysis. A case study approach to see how the phenomenon of digital capitalization through YouTube is carried out by social media operators. Furthermore, the results of the analysis are examined with the one-dimensional human perspective of Herbert Marcuse